2022
DOI: 10.1007/s00371-022-02671-3
|View full text |Cite
|
Sign up to set email alerts
|

A robust defect detection method for syringe scale without positive samples

Abstract: With the worldwide spread of the COVID-19 pandemic, the demand for medical syringes has increased dramatically. Scale defect, one of the most common defects on syringes, has become a major barrier to boosting syringe production. Existing methods for scale defect detection suffer from large volumes of data requirements and the inability to handle diverse and uncertain defects. In this paper, we propose a robust scale defects detection method with only negative samples and favorable detection performance to solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This syringe dataset captured by industrial cameras consists of 590 normal images and 567 defective images. Following [3], these defective images are artificially generated from normal images with various kinds of defects, including "broken", "length abnormal", "excessive", "width abnormal", "missing", and "other". Some typical syringe images are shown in Fig.…”
Section: Datasets and Compared Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This syringe dataset captured by industrial cameras consists of 590 normal images and 567 defective images. Following [3], these defective images are artificially generated from normal images with various kinds of defects, including "broken", "length abnormal", "excessive", "width abnormal", "missing", and "other". Some typical syringe images are shown in Fig.…”
Section: Datasets and Compared Methodsmentioning
confidence: 99%
“…The detailed procedures of the proposed method are listed as follows: Scale Extraction. We first extract the individual scales or regions of interest (ROIs) from the syringe images using the deep segmentation model in [3], only utilizing the non-defective syringe images, which can be easily collected.…”
Section: Unsupervised Syringe Scale Defect Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed approach could represent a key asset also for the rapid response to new virus variants, allowing for a fast and optimized mRNA design. There are numerous other examples where artificial intelligence and machine learning have started bringing value to the technical development of therapeutics: from using a similar sequence modeling strategy to increase the yield of protein vaccine production in cell cultures [ 56 ] to the automated inspection of product defects based on analysis of their automatically generated images with computer-vision technology [ 57 ].…”
Section: Key Enablers Of Acceleration and Pandemic Preparednessmentioning
confidence: 99%
“…Tabernik et al [16] also employed segmentationbased two-stage networks on the Kolektor surface-defect dataset and reached more advanced performance. In addition, many studies [17][18][19][20] have found that low-level visuospatial features in the network can improve the performance of semantic segmentation network. On this basis, Wang,et al [21] proposes to solve the edge blurring problem by leveraging multilevel representations during segmentation.…”
Section: Related Workmentioning
confidence: 99%